2017
DOI: 10.4172/2329-888x.1000181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polysaccharides from Mango’ Peel on Physiochemical and Sensory Properties of Non-Fat Yoghurts

Abstract: Plant polysaccharides derived from fruits and vegetables are natural fibre materials with a low calorie content that can be used as a healthy alternative to gum stabilisers and starches for structuring free-fat yoghurt. This study aims to evaluate the effect of the supplementation of polysaccharides from Mango' Peel (as fat replacers) on the quality attributes of free-fat yoghurt. Polysaccharides at 0.05, 0.10 and 0.15 g/100 mL of reconstituted milk, were used also carboxymethyl cellulose (CMC) with 0.15 g/100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
5
10
0
Order By: Relevance
“…This difference can be explained by the fact that the increasing percent of ulvan polysaccharide in synbiotic yogurt may be slightly inhibiting the activity of lactic acid bacteria; and the previous result for lactose content and fermentation time were appropriate with that explanation. These results in agreements with Al-Sheraji et al [12] who concluded that the acidity values of free fat yogurt enhanced with 0.15% mango polysaccharide was lower than that enhanced with 0.05 and 0.1% mango polysaccharide.…”
Section: The Changes Of Acidity and Ph Values Of Synbiotic Yogurt Enhsupporting
confidence: 92%
See 4 more Smart Citations
“…This difference can be explained by the fact that the increasing percent of ulvan polysaccharide in synbiotic yogurt may be slightly inhibiting the activity of lactic acid bacteria; and the previous result for lactose content and fermentation time were appropriate with that explanation. These results in agreements with Al-Sheraji et al [12] who concluded that the acidity values of free fat yogurt enhanced with 0.15% mango polysaccharide was lower than that enhanced with 0.05 and 0.1% mango polysaccharide.…”
Section: The Changes Of Acidity and Ph Values Of Synbiotic Yogurt Enhsupporting
confidence: 92%
“…Another reason is that the used ulvan polysaccharide contained different components which contributed in total solids of the resultant yogurt. The obtained results were in agreement with Al-Sheraji et al [12] who found that the addition of polysaccharide from mango peel increased the total solids of nonfat yogurt. Hussein et al [6] also reported that the enhanced yogurt with polysaccharide of Jew's-mallow had total solids content higher than control.…”
Section: Gross Composition Of Synbiotic Yogurt Enhanced With Ulvan Posupporting
confidence: 92%
See 3 more Smart Citations